Exosomes Derived From Epigallocatechin Gallate-Treated Cardiomyocytes Attenuated Acute Myocardial Infarction by Modulating MicroRNA-30a - Zhang, Chan; Gan, Xiaowen; Liang, Ronggan; Jian, Jie (Frontiers in Pharmacology, 2020)
Background: Ischemia-derived exosomes can restrict excessive autophagy by transferring microRNA-30a (miR30a) to cells. Reports have confirmed that epigallocatechin gallate (EGCG) alleviates acute myocardial infarction (AMI) by regulating autophagy; however, research evaluating the communication with cardiomyocytes and exosomes is lacking. This study aimed to explore whether exosomes derived from EGCG-treated cardiomyocytes mitigated AMI by adjusting miR30a to inactivate apoptosis and autophagy. Methods: Exosomes were extracted from cardiomyocytes, cultured either in control or AMI condition, with or without EGCG pretreatment. The exosome characteristics were analyzed by nanoparticle tracking analyses (NTA) and transmission electron microscopy (TEM). The change in miR30a in cells and exosomes was demonstrated by qRT-PCR. H9c2 or stable miR30a knockdown (miR30aKD) cell lines were incubated with exosomes derived from EGCG-treated cardiomyocytes in vitro or in vivo. The effect of EGCG and exosomes on I/R-induced cardiomyocyte apoptosis and autophagy was assessed. Results: EGCG improved the activity of cardiomyocytes, and increased average diameter, concentration, miR30a mRNA level, and specific protein expression in AMI-derived exosomes produced by cardiomyocytes. Moreover, the coincubation of AMI cells with EGCG or exosomes derived from EGCG-treated cardiomyocytes attenuated cardiomyocyte apoptosis and autophagy. Conclusions: The findings showed that EGCG upregulates miR30a, which was efficiently transferred via exosomes between cardiomyocytes, thereby contributing to the suppression of apoptosis and autophagy. By focusing on the cardiomyocyte microenvironment, we identified a new target of EGCG alleviating AMI by regulating apoptosis and autophagy.